Development of a capillary-modified naked-eye visual loop-mediated isothermal amplification method for the rapid detection of mpox virus and chikungunya virus - Luan, Junwen; Song, Shuai; Cheng, Chen; Li, Daoqun; Zhu, Liyuan; Cheng, Huixiang; Zhang, Leiliang (Frontiers in Microbiology, 2025)
The global emergence of mpox virus (MPXV) and chikungunya virus (CHIKV) has intensified the demand for advanced diagnostic methods. Rapid, sensitive, cost-effective diagnostic methods are crucial for preventing cross-border transmission and early containment of community spread. In this study, we developed a capillary modified Loop-mediated isothermal amplification (LAMP) assay for the identification of MPXV and CHIKV. This system employs capillaries as reaction vessels, offering advantages such as reduced reagent consumption and simplified operation. The capillary-driven liquid handling system also significantly reduces the frequency of lid openings during reagent transfer compared to standard LAMP protocols. This minimizes the risks of aerosol contamination and the associated false-positive outcomes that are inherent to conventional methods. Additionally, direct visual interpretation of the results without specialized instrumentation is achieved through integration of a leuco-hydroxynaphthol blue (LHNB) dye. This novel detection method targets the F13 gene of MPXV, the nsP1 gene of CHIKV, live vaccinia virus (VACV) and CHIKV viruses. Analytical sensitivity reached 10 copies/μL for MPXV F13 and 6 copies/μL for CHIKV nsP1. Because of the high level of laboratory biosafety required for MPXV culture, VACV was selected as a safe surrogate model for detection, where the E9L gene was selected to target all Orthopoxvirus (OPXV). The detection limits of infectious units for intracellular and extracellular viruses of VACV are 0.64 plaque-forming units (PFU) and 8 PFU, respectively. For CHIKV infection, the detection limits of infectious units for intracellular and extracellular viruses are 0.3 PFU and 0.068 PFU, respectively. The capillary modified LAMP assay achieves higher sensitivity to current gold-standard qPCR assays, while offering several advantages, including rapid turnaround time (results obtained within 30 min), minimal equipment requirements (single heating module), cost-effectiveness, visual readout compatibility, and no requirement for specialized personnel. This study confirmed the capacity of this improved LAMP colorimetric detection method. The system addresses critical gaps in resource-limited scenarios, offering a deployable solution for border quarantine stations and primary healthcare services–key nodes for intercepting cross-border transmission and mitigating localized outbreaks through timely case identification.